Computational design of a metal-based frustrated Lewis pair on defective UiO-66 for CO2 hydrogenation to methanol. Issue 43 (27th October 2020) - Yang, Kuiwei; Jiang, Jianwen
Abstract : An active FLP structure is computationally proposed through defect-engineering of UiO-66 for CO2 hydrogenation to CH3 OH. Abstract : Metal–organic framework (MOF)-based catalysts have shown enormous potential in CO2 conversion to high-value added chemicals. Herein, we report a density functional theory (DFT) study on CO2 hydrogenation to methanol (CH3 OH) on defective UiO-66, in which a frustrated Lewis pair (FLP) is created by removing one organic linker. The hydrogenation is considered a three-stage transformation: (1) CO2 is hydrogenated into formic acid (HCOOH); (2) HCOOH is converted to formaldehyde (HCHO) via hydrogenation and dehydration; (3) HCHO is hydrogenated into CH3 OH. The reaction mechanisms are investigated in detail by studying the optimized structures and the corresponding Gibbs energies for the elementary processes involved in the transformation. For CO2 hydrogenation to HCOOH, three pathways are computed comparatively. In Pathway I, adsorbed CO2 reacts with H2 to form HCOOH directly and this step features a high free energy barrier comparable to that in the gas phase. In the other two pathways, adsorbed H2 is first split into a proton (H + ) and a hydride (H − ) on the FLP, and then CO2 is hydrogenated into HCOOH via a stepwise mechanism (Pathway II) or a concerted mechanism (Pathway III). The DFT calculations reveal that the energy barriers in Pathway II and III are reduced significantly compared to that in Pathway I, and Pathway III is the most favourable for CO2 hydrogenation to HCOOH. Subsequent calculations suggest that the conversion of HCOOH to HCHO and further to CH3 OH is also facile via H2 dissociation and the concerted transfer of H + and H − to HCOOH and HCHO. These results highlight the importance of FLP-assisted heterolytic dissociation of H2 in promoting CO2 hydrogenation. This study suggests that the defective UiO-66 with a FLP might be a potential catalyst for CO2 hydrogenation and it could facilitate the bottom-up design of efficient MOF-based catalysts for CO2 utilization.